Preference weights for the spectrum of alcohol use in the U.S. Population. (1st April 2016) - Chavez, Laura J.; Bradley, Katharine; Tefft, Nathan; Liu, Chuan-Fen; Hebert, Paul; Devine, Beth
Highlights: Evaluated alcohol use and preference-based health-related quality of life (HRQOL). Report preference weights for spectrum of alcohol use in U.S. adult sample. Nondrinking respondents who were former drinkers had lowest self-reported HRQOL. Very severe unhealthy alcohol use not associated with lower HRQOL. Generic measures may not capture important differences in HRQOL for alcohol use Abstract: Background: Little is known about the cost-utility of population-based alcohol interventions. One barrier to research has been the lack of preference weights needed to calculate Quality Adjusted Life Years (QALYs). Preference weights can be estimated from measures of health-related quality of life (HRQOL). The objective of this study was to describe preference weights for the full spectrum of alcohol use. Methods: This cross-sectional study included participants in both the National Health Interview Survey (NHIS; 1999–2002) and the Medical Expenditure Panel Survey (MEPS; 2000–2003). The AUDIT-C alcohol screen was derived from NHIS with scores categorized into 6 groups (0, 1–3, 4–5, 6–7, 8–9, 10–12 points), ranging from nondrinking (0) to very severe unhealthy alcohol use (10–12). AUDIT-C scores were mapped to EQ-5D and SF-6D preference weights using the linked datasets and analyses adjusted for demographics. Results: Among 17, 440 participants, mean EQ-5D and SF-6D preference weights were 0.82 (95% CI 0.82–0.83) and 0.79 (95% CI 0.79–0.80), respectively. Adjusted EQ-5D preference weights for nondrinking (0.80; 95% CI 0.79–0.81) and moderate unhealthy drinking (0.85; 95% CI 0.84–0.86) were significantly different from low-risk drinking (0.83; 95% CI 0.83–0.84), but no other differences were significant. Results for the SF-6D were similar. Conclusions: This study provides EQ-5D and SF-6D preference weights for various alcohol use categories in a representative U.S. adult sample. However, neither measure suggested meaningful differences in HRQOL based on AUDIT-C categories. Self-reported alcohol consumption may not be associated with preference weights or generic instruments may not capture alcohol-related differences in HRQOL.